Peran Keluarga Dalam Meningkatkan Motivasi Kerja di PT Pertamina EP Sangatta - Yudhistira Anugerah Pratama; Louisiani Mansoni Isnajati; Farida Yuliaty; Kosasih Kosasih (LPPM Universitas Sangga Buana, 2025)
This study aims to analyze the role of family in increasing the work motivation of Pertamina Exploration and Production of Sangatta's employees which covers four dimensions, namely education, protection, affection, and economy. This study used a quantitative descriptive approach using slovin in determining the number of respondents. The results showed that the role of the family of Pertamina Exploration and Production of Sangatta's employees has been carried out well. This can be seen from the total respondent's answer score is 3,968. However, to optimize the increase in employee motivation, researchers suggest that families apply protection and economic as optimally as possible.